2020
DOI: 10.1088/2053-1591/ab6925
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of Zn-doping effects on phase stability and magnetic anisotropy of Ni-Mn-Ga alloys

Abstract: The effect of Zn doping on Ni-Mn-Ga magnetic shape memory alloy was studied by the firstprinciples calculations using exact muffin-tin orbital method in combination with the coherentpotential approximation and projector augmented-wave method. Trends in martensitic transformation temperature T M and Curie temperature T C were predicted from calculated energy differences between austenite and nonmodulated martensite, ΔE A−NM , and energy differences between paramagnetic and ferromagnetic state, ΔE PM−FM . Doping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
8
0
2
Order By: Relevance
“…The increased stability of NM martensite was also observed for Ni‐rich alloys by Zayak et al [ 95 ] and other authors. [ 62,147 ] The validity of this approach for predicting TnormalM was also confirmed for alloys with Fe and Co, [ 145,146 ] Al, [ 97 ] Pt, [ 61 ] Cu, [ 148 ] Zn, [ 124,149 ] Ti, [ 150 ] B, [ 122 ] and Co+Cu. [ 151 ] Some predictions without experimental comparisons are also available for Bi [ 150 ] and Mg alloying.…”
Section: Beyond a Perfect Lattice: Off‐stoichiometry Alloying And Ord...mentioning
confidence: 79%
See 3 more Smart Citations
“…The increased stability of NM martensite was also observed for Ni‐rich alloys by Zayak et al [ 95 ] and other authors. [ 62,147 ] The validity of this approach for predicting TnormalM was also confirmed for alloys with Fe and Co, [ 145,146 ] Al, [ 97 ] Pt, [ 61 ] Cu, [ 148 ] Zn, [ 124,149 ] Ti, [ 150 ] B, [ 122 ] and Co+Cu. [ 151 ] Some predictions without experimental comparisons are also available for Bi [ 150 ] and Mg alloying.…”
Section: Beyond a Perfect Lattice: Off‐stoichiometry Alloying And Ord...mentioning
confidence: 79%
“…Such CPA-based analyses are available for off-stoichiometric alloys, [154] as well as alloys with additional Fe, Co, Cu, [155] Al, [168] and Zn. [124] Calculations based on supercells have shown that the excess Mn atoms in the Ga sublattice prefer to be adjacent to each other, [118,121] but such configurations are hardly accessible at low temperatures due to the slow diffusion of Mn atoms. [110] In calculations, it is typically assumed that stoichiometric Ni 2 MnGa exhibits a perfect atomic order.…”
Section: Search For the Ground State Of Ni 2 Mngamentioning
confidence: 99%
See 2 more Smart Citations
“…The substantial hysteresis between the temperature of the martensitic transformation (during cooling) and the austenitic transformation (during heating) was very characteristic for the first-order temperature-driven transformation, especially in polycrystalline materials where the transition takes place in every single grain. Moreover, the martensitic transformation temperature was strongly dependent from the Gibbs free energy difference between the austenite and martensite phases and the addition of alloying elements may have significantly changed these energies [ 36 , 37 , 38 ]. In order to compare the transformation temperatures between the studied alloys, the average value of all temperatures ( M s , M f , A s , A f ) was calculated as: where T M is structural transformation temperature, M s and M f are martensitic transformation start and finish temperature, and A s and A f are austenitic transformation start and finish temperature.…”
Section: Resultsmentioning
confidence: 99%